Abstract 093: Carotid Stump Syndrome: an Insidious Source of Recurrent Ischemic Strokes - Evan M. Anderson; Gunjanpreet Kaur; Hanan Qaqish; Karthik Narayanan; Wilson Rodriguez; Brian Miremadi (Stroke: Vascular and Interventional Neurology)
Introduction Carotid stump syndrome (CSS) is a paradoxical phenomenon that occurs when there are repeated ischemic events in the carotid vascular territory despite demonstrated occlusion of the ipsilateral internal carotid artery (ICA). It is thought to be caused by turbulent blood flow in the patent stump of the occluded ICA creating microemboli which reach the brain through anastomotic channels and retrograde flow. We present a case of recurrent infarctions in setting of known ipsilateral ICA occlusion, who was diagnosed with carotid stump syndrome. Methods A male veteran in his 60s with a medical history of DVTs on apixaban, PVD, and ischemic stroke with residual right‐sided weakness, presented with worsening right‐sided weakness and difficulty with ambulation. Two months prior to the presentation he was diagnosed with acute infarcts in left frontal, parietal, and temporal lobes due to thromboembolism from left ICA occlusion. On presentation his neurological exam revealed right‐sided hemiparesis. MRI brain showed multiple acute and chronic cortical and subcortical infarcts in the left frontotemporoparietal lobes and lack of flow void in the left distal ICA. To further evaluate the dynamics of blood flow patient underwent a cerebral angiogram which confirmed the diagnosis of complete occlusion of left ICA and demonstrated reconstitution of the intracranial ICA through retrograde filling via the ophthalmic artery and anastomotic branches with the internal maxillary artery (IMax). For secondary prevention he was started on statin and aspirin while his home Apixaban was continued. Surgical and endovascular treatment approaches were discussed but the patient declined any intervention. In his four months follow up clinic visit he had no further concerns of recurrent strokes or new symptoms. Results Carotid stump syndrome is a rare cause of cerebral and retinal ischemia; however, it must be considered in patients with recurrent ischemic strokes and chronic ipsilateral ICA occlusion. Due to the patent proximal, or perhaps in some cases distal, carotid stump, there’s turbulent flow and hence the thrombus formation can occur. Hemodynamic and embolic factors attribute towards the microembolization from the proximal carotid stump through the external carotid artery (ECA), into the facial artery and IMax and their distal branches which anastomose with the ophthalmic artery, causing the emboli to end up in the major branches of the carotid terminus. If a distal stump is symptomatic, then the microemboli can readily end up in the distal ICA branches. In addition to medical management with DAPT or anticoagulation and high intensity statin, our literature review supports endovascular or surgical interventions due to reportedly good outcomes. Interventional approaches may include ECA‐ICA stenting with a covered stent or stent‐assisted coil embolization of the proximal stump. Surgical procedures include an endarterectomy on the ipsilateral ECA or contralateral ICA to increase collateral circulation. ECA‐ICA bypass is another option. Conclusion Carotid stump syndrome is a rare and underrecognized cause of recurrent ischemic strokes, though it is a potentially treatable entity. The therapeutic goals include medical management along with endovascular or surgical treatment whenever possible.